Desejos à deriva: os michês e a construção de masculinidades no Centro de João Pessoa - Lima, Wagner de Oliveira (2006)
This study proposes to analyze the construction of masculinities produced from michés who valid their gestural and discursive archetypes to present themselves for clients (PERLONGHER, 1987) in addition to constructed relationships in João Pessoa (PB) downtown space as fluid senses for builded-up places, the No-places (AUGE, 1994). Taking as a basis theoretical production comprehended as Gender, whereas relational categories, we discussed in this study the concept of masculinity taking as a reference the subordinate and hegemonic masculinity concept (CONNELL, 1995; KIMMEL, 1998) as well as this matrix feeding ways into society scope. The discussion larded throughout this study is about masculinity(ies). On one hand discussions about identity and ways of social interaction (CASTELLS, 2002), gender as relational category (SCOTT, 1991), subordinate and hegemonic masculinities (CONNELL 1995; KIMMEL, 1998). On the other hand No-places (AUGĖ, 1994). The masculinity lived among michês is associated to the Northeast man identity (ALBUQUERQUE, 2003) and also the patriarchal model "inheritance" lived since Brazil-Colony. Our investigation camp focused on Jollo Pessoa downtown, which the research took place practicing the participant observation, conduced towards eight michés and their agent. The informants selection criteria for the research were they had to practice male street prostitution in addition to visit downtown place often, to which lots of them converge from different parts of the city looking for homoerotic interactions. The masculinity has been the mainly way men are socialized in the world, since childhood. The analysis allowed us to confirm that michés effort is higher to keep the masculinity control over the bodies, discourses and practices than physical their effort resistance of doing daily trottoir, after all, masculinities for michés would be the reason to be in the world.